The SAGA histone acetyltransferase module targets SMC5/6 to specific genes - Mahrik, L; Stefanovie, B; Maresova, A; Princova, J; Kolesar, P; Lelkes, E; Faux, C; Helmlinger, D; Prevorovsky, M; Palecek, J J (Epigenetics & chromatin, 2023)
BACKGROUND: Structural Maintenance of Chromosomes (SMC) complexes are molecular machines driving chromatin organization at higher levels. In eukaryotes, three SMC complexes (cohesin, condensin and SMC5/6) play key roles in cohesion, condensation, replication, transcription and DNA repair. Their physical binding to DNA requires accessible chromatin. RESULTS: We performed a genetic screen in fission yeast to identify novel factors required for SMC5/6 binding to DNA. We identified 79 genes of which histone acetyltransferases (HATs) were the most represented. Genetic and phenotypic analyses suggested a particularly strong functional relationship between the SMC5/6 and SAGA complexes. Furthermore, several SMC5/6 subunits physically interacted with SAGA HAT module components Gcn5 and Ada2. As Gcn5-dependent acetylation facilitates the accessibility of chromatin to DNA-repair proteins, we first analysed the formation of DNA-damage-induced SMC5/6 foci in the Δgcn5 mutant. The SMC5/6 foci formed normally in Δgcn5, suggesting SAGA-independent SMC5/6 localization to DNA-damaged sites. Next, we used Nse4-FLAG chromatin-immunoprecipitation (ChIP-seq) analysis in unchallenged cells to assess SMC5/6 distribution. A significant portion of SMC5/6 accumulated within gene regions in wild-type cells, which was reduced in Δgcn5 and Δada2 mutants. The drop in SMC5/6 levels was also observed in gcn5-E191Q acetyltransferase-dead mutant. CONCLUSION: Our data show genetic and physical interactions between SMC5/6 and SAGA complexes. The ChIP-seq analysis suggests that SAGA HAT module targets SMC5/6 to specific gene regions and facilitates their accessibility for SMC5/6 loading.
Keywords: Histone H3K9ac acetylation; Histone Acetyltransferases; buněčné jádro; Genetic and protein–protein interactions; Gene regions; rDNA; SAGA histone acetyltransferase module; Carrier Proteins; DNA; chromozomy; Gcn5; acetyltransferasy; Ada2; Chromatin; Schizosaccharomyces pombe Proteins; Schizosaccharomyces pombe - proteiny; Chromatin accessibility; SMC5/6 complex targeting; Cell Cycle Proteins; Acetyltransferases; Cell Nucleus; proteiny buněčného cyklu; DNA repair; Schizosaccharomyces; Chromosomes; Nse3 KITE; chromatin; histonacetyltransferasy; transportní proteiny